Antipoliovirus activity of the organic extract of Eupatorium buniifolium: isolation of euparin as an active compound - Visintini Jaime, María Florencia (2013)
The antiviral activity of the organic extract (OE) of Eupatorium buniifolium against poliovirus type 1 was determined by in vitro assays with an effective concentration 50 (EC50) of 23.3 ± 3.3 µg/mL. Bioassay-guided fractionation of the OE allowed the isolation of an active principle that was identified by spectroscopic methods (1H- and 13C-NMR, EI-MS, UV, and IR spectroscopy) as the benzofuran euparin. The plaque reduction assay in Vero cells was used to assess the antiviral activity of euparin against poliovirus types 1, 2, and 3 with EC50 values of 0.47, 0.12, and 0.15 µg/mL, respectively. Moreover, this compound showed high selectivity indexes of 284.9, 1068, and 854.7, respectively. In order to identify the mechanism by which euparin exerts its antiviral activity, the virucidal effect, the pretreatment of Vero cells, and the time of action on one viral replication cycle were evaluated. Results obtained demonstrated that euparin exerts its effect during the early events of the replication cycle, from the virus adsorption to cells up to the first twenty minutes after infection. This is the first report on the presence of euparin in E. buniifolium and its antiviral activity.